PENGEMBANGAN MEDIA BOOKLET BERBASIS SETS MATERI SUMBER ENERGI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Putra, Vinda Kristian; Fatih, Mohamad; Niam, Fathul (STKIP Persada Khatulistiwa Sintang, 2024)
Learning media is an object or tool which can be used as an intermediary by teachers and accepted by recipients, namely students, in the teaching and learning process so that learning can run effectively and efficiently so that learning objectives can be achieved according to the desired curriculum. This sets-based booklet media was created as an alternative in learning science subjects. This stage consists of: analyze, design, development, implementation and evaluation. The stages in implementing research and development activities are contained in the ADDIE model. The results of validation of sets-based booklet media were carried out by several experts, such as media experts, material experts and language experts. The media expert's assessment of this learning media is based on two aspects (1) Clarity and (2) Appearance is